Pengaruh Neurotisme terhadap Fear of Missing Out pada Remaja Akhir Pengguna Media Sosial di Universitas Islam Bandung - Marelda Patricia Arlie Wibowo; Muhammad Ilmi Hatta (Bandung Conference Series: Psychology Science, 2023)
Abstract. Fear of Missing Out (FoMO) is the fear that someone feels that other people are enjoying more exciting activities or without their presence, the feeling arises because of other people's activity updates on social media. Individuals who tend to experience Fear of Missing Out (FoMO) more often are individuals who have the personality trait of neuroticism. The purpose of this study is to determine the effect of neuroticism on Fear of Missing Out (FoMO) in late adolescents who use social media. The approach used in this study is a non-experimental causality research design. The subjects used in this study were 403 late adolescents at the Islamic University of Bandung. The scale to measure the level of neuroticism used is the Big Five Personality Inventory and the fear of missing out scale. Quota sampling was used as a sample collection method in this study. The data analysis technique used was Simple Linear Regression Test. The results of regression testing show that neuroticism has a significant influence on Fear of Missing Out (FoMO). The coefficient of determination obtained in this study is .197 which indicates that the influence or ability of the Neuroticism variable in explaining the Fear of Missing Out (FoMO) variable is 19.7%. Abstrak. Fear of Missing Out (FoMO) adalah ketakutan yang dirasakan seseorang bahwa orang lain tengah menikmati kegiatan yang lebih seru atau tanpa kehadirannya, perasaan itu timbul karena pembaruan aktivitas orang lain di media sosial. Individu yang cenderung lebih sering mengalami Fear of Missing Out (FoMO) adalah individu yang memiliki trait kepribadian neurotisme. Tujuan penelitian ini adalah untuk mengetahui pengaruh neurotisme terhadap Fear of Missing Out (FoMO) pada remaja akhir pengguna media sosial. Pendekatan yang digunakan dalam penelitian ini adalah desain penelitian kausalitas non-eksperimental. Subjek yang digunakan dalam penelitian ini sebanyak 403 remaja akhir di Universitas Islam Bandung. Skala untuk mengukur tingkat neurotisme yang digunakan yaitu Big Five Personality Inventory dan skala fear of missing out. Quota sampling digunakan sebagai metode pengumpulan sampel dalam penelitian ini. Teknik analisa data yang digunakan adalah Uji Regresi Linier Sederhana. Hasil pengujian regresi menunjukkan bahwa neurotisme memiliki pengaruh yang signifikan terhadap Fear of Missing Out (FoMO). Nilai koefisien determinasi yang diperoleh dalam penelitian ini sebesar .197 yang menunjukkan bahwa pengaruh atau kemampuan variabel Neurotisme dalam menjelaskan variabel Fear of Missing Out (FoMO) sebesar 19.7%.